Review on bacterial outer membrane vesicles: structure, vesicle formation, separation and biotechnological applications - Xiaofei Zhao; Yusen Wei; Yuqing Bu; Xiaokai Ren; Zhanjun Dong (Microbial Cell Factories)
Abstract Outer membrane vesicles (OMVs), shed by Gram-negative bacteria, are spherical nanostructures that play a pivotal role in bacterial communication and host-pathogen interactions. Comprising an outer membrane envelope and encapsulating a variety of bioactive molecules from their progenitor bacteria, OMVs facilitate material and informational exchange. This review delves into the recent advancements in OMV research, providing a comprehensive overview of their structure, biogenesis, and mechanisms of vesicle formation. It also explores their role in pathogenicity and the techniques for their enrichment and isolation. Furthermore, the review highlights the burgeoning applications of OMVs in the field of biomedicine, emphasizing their potential as diagnostic tools, vaccine candidates, and drug delivery vectors.